Exiles in Brussels. Last row: Lazarevic; couple seated right: Iturbe and Molina, man with guitar: Ocaña; at his right: Ascaso; leady left in centre: girlfriend of Ascaso
Exiles in Brussels. Last row: Lazarevic; couple seated right: Iturbe and Molina, man with guitar: Ocaña; at his right: Ascaso; leady left in centre: girlfriend of Ascaso.